Stroke and Coronary Heart Diseases, Global and Asian Trend and Risk Factors -A Perspective (Medicine Today, 2022)
Introduction: Cardiovascular disease (CVD) is the leading cause of death in the world, accounting for 30% of deaths globally. CVD is a group of conditions affecting the functions of the heart, blood vessels or both. The major cardiovascular diseases include coronary heart disease (CHD), stroke, hypertension, heart failure and peripheral vascular diseases. Distribution of CHD and stroke is different in different regions of the world, especially western high-income, Asian and other countries. The Asian prevalence also not homogenous. Estimated number of deaths due to CVD worldwide will projected to 23.4 million, comprising 35% of all deaths in 2030. Significant increase in prevalence of coronary heart diseases (CHD) have been observed in the Asia including Bangladesh, but stroke in some regions of the world. Objectives: (1) Identification of cases and risk factors in different geographical area (2) Reduction of morbidity and mortality by proper treatment and management of modifiable risk factors.Materials and Methods: This observational study was done through using evidence from the published study articles of CVD in national and international journals, electronic databases such as MEDLINE, EMBESE and PUBMED. We also manually checked references of relevant publications of stroke and CHD.Study period: Jan2019-Dec2019.Results: Approximately 940 million people in the high income countries, where CHD is the dominant form of CVD which is 2–5 times higher than stroke. In the USA, Canada, Australia, New Zealand, Italy, France and Spain CVD death rates are very low. The highest death CHD rate is in Finland, Ireland, Scotland, Norway, Sweden of the European countries. In Eastern Europe and most of the Asia, the rate of coronary arterial diseases are rapidly increasing. Japan the Asian high income country the death ratio of stroke and CHD is 3:1.The East Asia and the pacific including China CVD is the major cause of death, where stroke dominating. People in South Asia including India and Bangladesh the coronary diseases are increasing alarmingly, where CVD death increase 30%over the preceding decade and the dominant form is CHD. In the central Asia, specially Uzbekistan, Kazakhstan, Tajikistan both CHD and stroke are very high. In Latin America death from CHD (35%) higher than stroke (29%). In the Middle East and North Africa, CHD responsible for 17% and stroke 7%of all death.Conclusion: Asian countries have disproportionately high morbidity and mortality from stroke with increasing tendency to CHD, but CHD in Western countries which may be due to complex interaction of genetic and environmental factors, smoking, hypertension and metabolic abnormalities. Death rate is higher in male sex from both CHD and stroke worldwide.Medicine Today 2022 Vol.34(1): 27-35